Pengaruh Variasi Latihan Wall Pass Terhadap Ketepatan Passing dalam Permainan Sepak Bola - Ainun Nizar, Daffa; Fauzi, Rizal Ahmad; Rukmana, Anin (Universitas Hamzanwadi, 2024)
The problem of this research is that novice players often have difficulty in making targeted passes. This condition is certainly detrimental to their team because the ball is easily captured by the opponent. The purpose of the study was to examine the effect of wall pass training on passing accuracy. This research uses an experimental method. This research design is one group pretest-postest design. The population of this study were all students in extracurricular football at SDN Sukamaju. This sample uses purposive sampling, namely 20 people. Data analysis uses data normality test, paired sample T-Test test, r-square regression test. The instrument uses a measurement test. The results of the study, namely the pretest, obtained an average value of 8.00, the lowest value was 6, the highest value was 12, and the standard deviation was 2.077. For the posttest, the average value was 17.90, the lowest value was 15, the highest value was 22, and the standard deviation was 1.944. Got a sig value of 0.001 < 0.05. So it can be concluded that there is an effect of wall pass training on the passing accuracy of extracurricular football members of SDN Sukamaju.